The Pentecostal Movement, its Challenges and Potential - Rosik, Mariusz (Verbum Vitae, 2015)
Review: Nigel Paul Willis, The Pentecostal Movement, its Challenges and Potential (Internationale Theologie / International Theology 17; Frankfurt am Main et al.: Peter Lang 2013)